1990
DOI: 10.1080/00913367.1990.10673190
|View full text |Cite
|
Sign up to set email alerts
|

Mothers' Communication Orientation and Consumer-Socialization Tendencies

Abstract: This study examines parent-child communication patterns and mothers' consumer-socialization tendencies. Results indicate mothers' concept-orientations are related to number of goals, discussing adlieTtising, cooiewing, coshopping, childrens influence, yielding, and granting children consumer independence. In contrast, socio-orientations are related to limits on children's TV exposure and refusing requests.Following charges by consumer groups about effects of marketing activities (especially TV advertising) on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
79
0
3

Year Published

1993
1993
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(86 citation statements)
references
References 24 publications
2
79
0
3
Order By: Relevance
“…Past research has also uncovered connections between mother-child communication patterns and mothers' socialization practices such as mediation of children's media use, co-shopping, and yielding to requests as well as granting purchasing independence and consideration of children's opinions (Carlson, Grossbart, & Walsh, 1990;Rose, Bush, & Shoham, 2002).…”
Section: Background Family Communication Patternsmentioning
confidence: 96%
See 2 more Smart Citations
“…Past research has also uncovered connections between mother-child communication patterns and mothers' socialization practices such as mediation of children's media use, co-shopping, and yielding to requests as well as granting purchasing independence and consideration of children's opinions (Carlson, Grossbart, & Walsh, 1990;Rose, Bush, & Shoham, 2002).…”
Section: Background Family Communication Patternsmentioning
confidence: 96%
“…One aspect of consumer socialization that has attracted considerable research involves the issues of parent-child interactions (Carlson & Grossbart, 1988;Carlson, Grossbart, & Stuenkel, 1992;Mandrik, Fern, & Bao, 2005;Moschis, Moore, & Smith, 1984;Rose, Boush, & Shoham, 2002). Acknowledging the critical role parents play in children's consumer socialization, these studies focus on how parent-child interaction styles and orientations are linked to parents' socialization practices and children's consumer behavior, including their consumption/purchase autonomy, influence and participation in family purchase processes, use of market information, and attitudes toward advertising.Two aspects of parent-child interactions have emerged prominently in past research on child development and consumer socialization, namely, parenting style (Carlson, Grossbart, & Stuenkel, 1992;Carlson & Grossbart, 1988;Darling & Steinberg, 1993;Rose, 1999;Steinberg et al, 1991) and family communication patterns (FCP) (Carlson, Grossbart, & Walsh, 1990;Carlson, Grossbart, & Stuenkel, 1992;Moschis, 1985;Rose, Boush, & Shoham, 2002;Rose, Bush, & Kahle, 1998). The present study provides a focus on the latter.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…This is similar to concept-oriented communications (Moore and Moschis 1981;Moschis 1985), where debate through open discussion of ethical issues is encouraged and furthers children's own critical thinking about online issues (Carlson et al 1990, Laczniak et al 1995. For example, research has shown that teens' discussion with their parents leads to higher levels of privacy concern (Youn 2008).…”
Section: Encouraging Verbalization Parenting Stylementioning
confidence: 99%
“…A gyerek fogyasztói szocializációjára tekintettel fontosabb szerepe van a kommunikáció módjának, mint az interakció gyakoriságának és mennyiségének (Carlson et al, 1990;Moschis -Moore, 1979;Moschis et al, 1984;Moschis et al, 1986). A családi kommunikációs mintáza-tok skála (family communication patterns scale) fogyasztói magatartásra adaptált verzióját is létrehozták (Moschis -Moore, 1979), és számos fogyasztói magatartást érintő kutatásban találkozhatunk vele (Caruana -Vassallo, 2003;Kim et al, 2009;Clarke, 2008).…”
Section: Az Intézményi Bizalom Mint a Versenyelőny Fogyasztói Forrásaunclassified